INFLUENCE OF THE MACROSTRUCTURE ON SEGREGATION OF THE STEEL INGOT - O. S. Komarov; O. V. Rozenberg; N. I. Urbanovich; K. E. Baranowski (Литьë и металлургия)
A theoretical analysis of the influence of carbon content in the steel and nature of macrostructure on segregation of impurities in the crystallization process were made. It is shown that increase of carbon content and transgranular macrostructure creation degree of segregation is being increased. A comparison of sulfur segregation in the ingot with equiaxial and transgranular structure was carried out and the theoretical points were confirmed.